ANTESEDEN MINAT BERKUNJUNG ULANG (Studi pada Cagar Budaya Bedung Lawang Sewu Semarang) - Sopyan, Sopyan; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2015)
This research was motivated by a lot of visitor complaints after visiting to Cagar Budaya Lawang Sewu in form of critics and suggestions. It indicates there are unsatisfactory feelings after their visit to Cagar Budaya Lawang Sewu that could be because of less attractive and decreasing services quality from the management. This research is aiming to analyze the effect of destination attraction and services quality toward visitor’s satisfaction and intent to revisit.zThis research using descriptive and quantitative for data analyze. The samples for this research are 385 visitors that visited Cagar Budaya Gedung Lawang Sewu. Data was collected using questionnaires which tested the validity and reliability. The data was analyzed using multiple regression. The result of descriptive analysis shown that tourism attraction, services quality, visitor’s satisfaction, and intention to revisit Cagar Budaya Lawang Sewu classified as moderate. Statistical tests shown visitor’s satisfaction variable is affecting positively toward intention to revisit variable (hypothesis 1 is accepted), tourism attraction variable is affecting positively toward visitor’s satisfaction (hypothesis 2 is accepted), services quality variable is affecting positively toward visitor’s satisfaction (hypothesis 3 is accepted), tourism attraction is affecting positively toward intention to revisit (hypothesis 4 is accepted), Variabel daya tarik berpengaruh positif terhadap minat berkunjung ulang (hipotesis 4 diterima), and services quality variable is affecting positively toward intention to revisit (hypothesis 5 is accepted).